Integrating Fire Prevention Strategies with Industrial Hygiene to Enhance Workplace Safety in Textile Industries - Utomo, Bekti (International Journal of Engineering, Science and Information Technology, 2025)
The textile industry in Indonesia is an economic sector that contributes significantly to exports and employment but has serious challenges related to occupational safety and health (OHS), especially in fire prevention and industrial hygiene. This study aims to analyze integrating fire prevention strategies with industrial hygiene practices to improve occupational safety in the textile sector. The method used is a case study of several textile companies in Indonesia with an analysis of the implementation of OHS policies, fire control technology, and its impact on worker safety. The results showed that companies implementing an integrated OHS management system experienced fewer fire incidents and safer working conditions. Key factors supporting this success include utilizing automatic fire detection technology, improved ventilation, and safety training for workers. In addition, government regulations and company management's awareness of adopting occupational safety standards play an essential role in the effectiveness of OHS programs. In conclusion, integrating fire prevention strategies with industrial hygiene is critical for improving occupational safety and health in Indonesia's textile industry. Recommendations include strengthening company policies, improving workforce training, and utilizing modern fire risk management and industrial hygiene technology. The findings are expected to contribute to developing more effective and sustainable OHS policies in the national textile industry.